Monitoring Detak Jantung pada Web Server Menggunakan Sensor Oximeter 30102 dan Nodemcu - Sujono Sujono; Ahmad Daud Al-Faatih (Router : Jurnal Teknik Informatika dan Terapan, 2025)
This research aims to design a web server-based heart rate monitoring system, which enables real-time heart rate monitoring from a remote location. The system utilizes a heart rate sensor connected to a microcontroller to measure and transmit heart rate data to a web server via an internet connection. The data obtained can be accessed directly by the user through a web-based interface, thus facilitating the monitoring of individual health conditions in an efficient manner. In addition, the system is equipped with a notification feature that alerts the user if any irregularities in the heart rate are detected, such as beating too fast or slow. As such, the system has the potential to increase alertness and speed up medical action if needed. The development of this system shows significant potential in supporting technology-based health applications, both for personal use and in a broader healthcare context. It is hoped that the system can contribute towards the development of more integrated and accessible health monitoring solutions.